Exploring the best possible route of infection of Verotxin producing Escherichia coli in development of experimental gastroenteritis among streptomycin treated murine model - Mosharraf, Fahareen Binta; Ahsan, Chowdhury Rafiqul; Nessa, Jamalun; Yasmin, Mahmuda (Journal of Bangladesh Academy of Sciences, 2015)
The prevalence of Escherichia coli O157:H7 induced bacteremia generate a critical problem in modern medical therapy for bacterial infections. This study sought to find out the best possible route and dose of E. coli 0157:H7 infection in experimental murine model by periodic stool and blood culture count of relevant bacterial strains. Streptomycin treated mouse model were used for investigating the clinical manifestation exerted by stx1A and stx2A positive E. coli O157:H7 with increasing doses applied through three alternative routes (oral, intramuscular and intraperitoneal). The highest titer of orally added E. coli 0157:H7 among five test doses started showing symptoms at the earliest time and reached moribund condition about 48 hours just before being dead. The oral way of E.coli O157:H7 at the dose of 100 ml suspension containing 1 ´ 109CFU ml-1 was taken as the most potent concentration in producing bacterial fatality and hence was selected as the minimum lethal dose (MLD). Journal of Bangladesh Academy of Sciences, Vol. 39, No. 1, 53-58, 2015